1979
DOI: 10.1136/thx.34.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Peak flow rate records in the diagnosis of occupational asthma due to colophony.

Abstract: Peak expiratory flow rate (PEFR) has been measured hourly from waking to sleeping in 29 workers with respiratory symptoms exposed to the fumes of soft soldering fluxes containing colophony (pine resin). Thirty-nine records of mean length 33 days have been analysed, and the results compared with the occupational history and bronchial provocation testing in the same workers. From (Schilling, 1956). Symptoms most severe on the first day of the working week are seen in a wide range of diseases where fever is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Development set 1 was the largest with all types of PEF record being represented including the most difficult type -namely, those which were equivocal for the presence of a work-related effect (14%) -and 50% were not thought to show a workrelated effect. A similar distribution of PEF records was seen in development set 2 Expert assessed group (overall weighted score) Figure 4 Comparison of visual weighted whole record scores with OASYS-2 scores for the development set 2. Cut off point Figure 5 Curve used to determine the cut offpoint for whc maximises sensitivity ( Factors which reduce the sensitivity and five records came from specificity of analysis by OASYS-2 include the upational asthma, and fact that it still relies on self-recorded PEF ded 2-51 in two, both of which suffers from problems of poor technique office workers who gave and sometimes, when compensation is an issue, y symptoms on the ques-frank falsification.…”
Section: Resultssupporting
confidence: 63%
“…Development set 1 was the largest with all types of PEF record being represented including the most difficult type -namely, those which were equivocal for the presence of a work-related effect (14%) -and 50% were not thought to show a workrelated effect. A similar distribution of PEF records was seen in development set 2 Expert assessed group (overall weighted score) Figure 4 Comparison of visual weighted whole record scores with OASYS-2 scores for the development set 2. Cut off point Figure 5 Curve used to determine the cut offpoint for whc maximises sensitivity ( Factors which reduce the sensitivity and five records came from specificity of analysis by OASYS-2 include the upational asthma, and fact that it still relies on self-recorded PEF ded 2-51 in two, both of which suffers from problems of poor technique office workers who gave and sometimes, when compensation is an issue, y symptoms on the ques-frank falsification.…”
Section: Resultssupporting
confidence: 63%
“…This is both sensitive and specific [2][3][4][5][6]. It was originally suggested that PEF measurement should be performed every 2 h whilst awake for a minimum of 4 weeks, including periods at and away from work [3].…”
mentioning
confidence: 99%
“…This can happen in individuals displaying only an immediate reaction to exposure; however, many other patterns of response are seen. Late reactions occur frequently in occupational asthma and may not become evident for many hours after exposure has commenced; symptoms may not occur until the end of a shift, do not fully recover overnight, and may progressively worsen through the working week [12,13]. In a study on occupational asthma in an electronics factory, eight out of 58 workers with wheeze or breathlessness that improved at the weekend described their symptoms as commencing o7 h after the beginning of their shift.…”
Section: Discussionmentioning
confidence: 99%